2017
DOI: 10.1007/s10549-017-4265-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin versus placebo on vitamin B12 metabolism in non-diabetic breast cancer patients in CCTG MA.32

Abstract: Background Metformin is associated with low levels of vitamin B12 (VitB12) in patients with diabetes. The CCTG/MA.32 trial investigates effects of metformin vs placebo on breast cancer (BC) outcomes in non-diabetic high risk BC patients. We analyzed VitB12 at baseline and after 6 months of metformin (versus placebo) in the first 492 patients with paired blood samples. Methods VitB12 was analyzed centrally in baseline and 6 month fasting plasma. Levels<181pmol/L were considered deficient, 181 to 221pmol/L bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Homocysteine, which is converted to methionine in the presence of VB12, is a marker for the activity of the vitamin. Some studies have found that the serum level of homocysteine was unaltered, whereas that of VB12 was reduced in patients treated with metformin, suggesting that the depletion of the vitamin was not sufficient to affect its biological actions in the body. The relationship between metformin use and both VB12 deficiency and the risk of associated health problems thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine, which is converted to methionine in the presence of VB12, is a marker for the activity of the vitamin. Some studies have found that the serum level of homocysteine was unaltered, whereas that of VB12 was reduced in patients treated with metformin, suggesting that the depletion of the vitamin was not sufficient to affect its biological actions in the body. The relationship between metformin use and both VB12 deficiency and the risk of associated health problems thus remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to former studies, it was more than proposed durations for onset of metformin effectiveness on serum level of Vitamin B12. In the study of Lohmann [23], the level of Vitamin B12 significantly decreased following to metformin intake compared to placebo. In contrast, in our results no relationship was seen between metformin use duration and Vitamin B12.…”
Section: Discussionmentioning
confidence: 96%
“…17,18 Some studies have found unchanged blood homocysteine even with decreased vitamin B12 in individuals on metformin therapy. [18][19][20] On the contrary, many studies demonstrated homocysteine rise despite the metformin-induced vitamin B12 diminution. 16,21 The discrepancy among these studies indicates that additional factors like age, nutritional status, food habits, metformin dosage are accountable for metformin-induced vitamin B12 reduction.…”
Section: Discussionmentioning
confidence: 99%